Malnutrition and Sarcopenia Combined Increases the Risk for Mortality in Older Adults on Hemodialysis - Macedo, Catarina; Amaral, Teresa F.; Rodrigues, Juliana; Santin, Fernanda; Avesani, Carla Maria (Frontiers in Nutrition, 2021)
Aim: Sarcopenia and malnutrition are highly prevalent in older adults undergoing hemodialysis (HD) and are associated with negative outcomes. This study aimed to evaluate the role of sarcopenia and malnutrition combined on the nutritional markers, quality of life, and survival in a cohort of older adults on chronic HD. Methods: This was an observational, longitudinal, and multicenter study including 170 patients on HD aged >60 years. Nutritional status was assessed by 7-point-subjective global assessment (7p-SGA), body composition (anthropometry and bioelectrical impedance), and appendicular skeletal muscle mass (Baumgartner's prediction equation). Quality of life was assessed by KDQoL-SF. The cutoffs for low muscle mass and low muscle strength established by the 2019 European Working group on sarcopenia for Older People (EWGSOP) were used for the diagnosis of sarcopenia. Individuals with a 7p-SGA score ≤5 were considered malnourished, individuals with low strength or low muscle mass were pre-sarcopenic, and those with low muscle mass and low muscle strength combined as sarcopenic. The sample was divided into four groups: sarcopenia and malnutrition; sarcopenia and no-malnutrition; no-sarcopenia with malnutrition; and no-sarcopenia and no-malnutrition. Follow-up for survival lasted 23.5 (12.2; 34.4) months. Results: Pre-sarcopenia, sarcopenia, and malnutrition were present in 35.3, 14.1, and 58.8% of the patients, respectively. The frequency of malnutrition in the group of patients with sarcopenia was not significantly higher than in the patients without sarcopenia (66.7 vs. 51.2%; p = 0.12). When comparing groups according to the occurrence of sarcopenia and malnutrition, the sarcopenia and malnutrition group were older and presented significantly lower BMI, calf circumference, body fat, phase angle, body cell mass, and mid-arm muscle circumference. In the survival analysis, the group with sarcopenia and malnutrition showed a higher hazard ratio 2.99 (95% CI: 1.23: 7.25) for mortality when compared to a group with no-sarcopenia and no-malnutrition. Conclusion: Older adults on HD with sarcopenia and malnutrition combined showed worse nutritional parameters, quality of life, and higher mortality risk. In addition, malnutrition can be present even in patients without sarcopenia. These findings highlight the importance of complete nutritional assessment in patients on dialysis.